The influence of physical training and other factors on the subjective rating of perceived exertion - Ekblom, B.; Golobarg, A. N. (Acta Physiologica Scandinavica, 1971)
The relationship between the subjective rating of perceived exertion (RPE) and different physiological variables during work were investigated in 19 healthy subjects under the following conditions: 1) after heart rate (HR) has been experimentally changed during work by the use of autonomic nervous system blocking agents. 2) during different types of physical work and 3) before and after an 8 week period of physical training, respectively. In most work situations, HR mirrors the physical strain subjectively experienced. However, this good correlation between HR and RPE was altered during the experiments with blocking agents. Therefore, a tachycardia as such is not the primary factor in the setting of HR during exercise — RPE was higher for a given level of oxygen uptake during arm work than during leg work, as well as during bicycling compared to running or swimming. A better correlation was found in these experiments between RPE and blood lactate concentration. After training, and in parallel to the decrease in HR at submaximal work loads, RPE was lower for a given level of oxygen uptake, but was the same when related to the "relative" (per cent of maximum) oxygen uptake. Abstract from author